Mapping and Functional Analysis of a Maize Silkless Mutant sk-A7110 - Zhao, Yan; Zhang, Yongzhong; Wang, Lijing; Wang, Xueran; Xu, Wei; Gao, Xianyu; Liu, Baoshen (Frontiers in Plant Science, 2018)
The maize (Zea mays) stigma, which is commonly known as silk, is indispensable for reproduction and thus for grain yield. Here, we isolated a spontaneous mutant sk-A7110, which completely lacks silk; scanning electron microscopy showed that the sk-A7110 pistils degenerated during late floret differentiation. Genetic analysis confirmed that this trait was controlled by a pair of recessive nuclear gene and sk-A7110 was mapped to a 74.13-kb region on chromosome 2 between the simple sequence repeat markers LA714 and L277. Sequence analysis of candidate genes in this interval identified a single-nucleotide insertion at position 569 downstream of the transcriptional start site in Zm00001d002970, which encodes a UDP-glycosyltransferase; this insertion produces a frameshift and premature translational termination. RNA-sequencing analysis identified 258 differentially expressed genes (DEGs) between sk-A7110 and the wild type, including 119 up- and 139 down-regulated genes. Interestingly, most DEGs related to jasmonic acid (JA) synthesis were up-regulated in the mutant compared to wild type. Consistent with this, the JA and JA-Isoleucine (JA-Ile) contents were significantly higher in sk-A7110 ears than in wild type. Our identification of the sk-A7110 mutant and the responsible gene will facilitate further studies on female infertility research or maize breeding.